The scientific and sociocultural value of citizen science - Daniel, Karis Amrita (Department of Biological Sciences, 2025)
At its best, conservation science serves as an interface between multiple disciplines, bringing together innovation and insight from the humanities, arts, business and economics, health, natural and social sciences to address the most pressing challenges facing the planet and its biodiversity. Conservation is also unique in its ability to transcend the academic. Subdisciplines such as biological citizen science involve non-academic individuals in data collection and as co-creators in research design and implementation. There is wide theoretical appeal to these initiatives, as they may simultaneously generate enough data for fine-scale biological monitoring and, through community engagement, promote the democratic generation and dissemination of knowledge. However, despite their potential within both the scientific and sociocultural realms, the regional scale impacts of citizen science initiatives in continental Africa remain poorly understood. Studying local citizen science initiatives affords opportunities to gain an understanding of their impact; within the African context, citizen science participants contribute to African Bird Atlas Projects in fifteen countries by compiling comprehensive avian species checklists at a fine geographic scale. Two projects are of particular interest for analysis: The Second Southern African Bird Atlas Project (SABAP2), and the Nigerian Bird Atlas Project (NiBAP). SABAP2 occupies a unique position as a long-term African citizen science project with ample data for statistical analyses. NiBAP employs an innovative grassroots approach to atlasing and hosts an enthusiastic and growing community of citizen science participants. In addition to impressive datasets, 'atlasers' in South Africa and Nigeria are a wealth of information regarding the personal- and community-level values surrounding participation and motivation. Furthermore, variations in project structure and cultural contexts between SABAP2 and NiBAP allow for some comparison of the values of participants between subprojects and contribute towards an understanding of the broader values of African Bird Atlas Project participants. In light of this potential, this thesis aims to examine the scientific and sociocultural contributions of SABAP2 and NiBAP to the work of conservation—namely achieving fine-scale species monitoring and advancing the democratic generation and sharing of scientific knowledge—within continental Africa. I examine the quality of data collected by a community of SABAP2 atlasers in Hessequa, South Africa, and assess their value in monitoring species population trends. I ask 1. Does systematic atlasing improve the temporal quality of atlas data for monitoring? and 2. Can these data detect trends in species populations and inform local response? Then, I explore values to nature expressed by atlasers and non-citizen science participants in both Hessequa, South Africa, and Jos, Nigeria. I ask the following two questions: 1. Does the type and frequency of values (instrumental, intrinsic, and relational) differ between participants and non-participants, and between cultural contexts?, and 2. what relational values (if any) are linked to participant motivation? Results demonstrate the ability of SABAP2 data to support biodiversity monitoring at a local scale, and show the potential for democratising research by including participants in data collection, analysis and application. The study of values and motivations emphasises the particular importance of relational values in connection with participant motivations and human-nature relationships broadly. Overall, the findings of this research demonstrate the ability of African Bird Atlas Projects and similar initiatives to meet the challenges of contemporary conservation, and lay a foundation for future research into the practical application of co-created monitoring schemes and incorporating values into the design of both citizen science projects and conservation interventions